(untitled) (Global Journals of Research in Engineering, 2012)
Exhaust gas recirculation (EGR) is a designed widely used system to reduce the exhaust emissions, particularly nitrogen oxides (NOx). At high temperatures, the nitrogen and oxygen in the engine combustion chamber can chemically combine to form NOx, which, when combined with hydrocarbons and the presence of sunlight, produce an ugly haze known commonly as smog. The EGR system recirculates a fraction of exhaust gases into the intake manifold where it mixes with the fresh incoming charge. By diluting the air- fuel charge, peak combustion temperatures and pressures are reduced resulting in a reduction of NOx concentration. In this paper, an experimental study was conducted to observe the effect of different quantities of EGR on emission and performance of four- stroke single cylinder hydrogen fueled spark- ignition engine with different excess- air ratio. Experiments were carried out for mass flow measuring of EGR with simplifying adjustment (manual designed EGR system) on the engine. Measurement results with higher EGR rates indicate a drastically reduction of NOx, especially with richer mixtures (about 60% NOx reduction). It was also observed an increase in specific fuel consumption of about 8%, a reduction in an indicated mean effective pressure (about 15%) and a reduction in an engine cylinder maximum pressure of about 19%.